Functional characterization of the \(OsSWEET13 \) promoter involved in the infection of \( Xanthomonas oryzae \) pv. \(oryzae (Xoo) \) in rice cultivar TBR225 - Phuong Ngoc, Pham; Lan Dai, Tran; Thi Hanh, Do; Quang Huy, Nguyen; Phuong, Nguyen Duy (Academia Journal of Biology, 2022)
Xanthomonas oryzae pv. oryzae (Xoo) causes severe bacterial leaf blight (BLB) disease to many Vietnamese major rice cultivars, including the TBR225. OsSWEET13 belongs to group III of the OsSWEET gene family encoding sugar transport proteins, which is considered one of the “susceptibility” genes (S genes) necessary for BLB disease. In this study, the rice cultivar TBR225 was determined to be susceptible to 19/20 Vietnamese Xoo isolates collected from the Northern provinces. Two of the three tested isolates (VXO_60 and VXO_96 isolates) were shown to up-regulate OsSWEET13 upon the Xoo infection of the TBR225 cultivar. The TBR225 OsSWEET13 promoter was isolated for sequencing analysis. The isolated DNA fragment was 615 bp in size, contained an effector binding element (EBE) PthXo2 that was recognized by the type III-secretory transcription activator-like (TAL) proteins of the Xoo. This promoter showed a similarity of more than 99% to the published OsSWEET13 promoter sequences (AP014967.1 and CP018167.1). Our findings are basic for the generation of highyielding rice varieties with resistance to BLB disease by genetic engineering in Vietnam.